Phacoemulsification surgery by a nationally-trained cataract surgeon of Nepal - Bajimaya, S; Sharma, B R; Shrestha, J B; Maharjan, I M; Matsushima, H; Akura, J (Nepalese Journal of Ophthalmology, 2012)
Introduction: A one month phacoemulsification training course had been implemented by the Nepal Netra Jyoti Sangh (NNJS) in collaboration with Association for Ophthalmic Cooperation to Asia, Japan (AOCA). Objective: To evaluate the visual outcomes of phacoemulsification surgery by a nationally trained surgeon in Nepal. Materials and methods: A retrospective study of patients that underwent phacoemulsification with foldable intraocular lens implantation during a period of 18 months was carried out. Cases that had a six-week follow-up period were included. Effective phaco time (EPT), intra-operative and postoperative complications were noted. Uncorrected visual acuity (UCVA) at day 1 and best corrected visual acuity (BCVA) at week 6 were noted. The data were analyzed using SPSS 11.5. Results: A total of172 patients that had completed a 6 week follow-up evaluation were included in the study. The mean age of patients was 57.12±10.19 years. The mean effective phaco time (EPT) was 9.74±7.41 seconds. Posterior capsule rupture (PCR) with vitreous loss occurred in 2 eyes (1.2%), Descemet’s membrane detachment in 1 eye (0.6%), capsulorhexis extension in 1 eye (0.6%) and wound site thermal injury (WSTI) occurred in 3 eyes (1.7%). Postoperative complications were mild to moderate striate keratopathy (9/ 172), corneal edema (1/172), corneal epithelial defect (1/172) and uveitis (1/172). At 6 weeks post-operatively, 165 eyes (95.9%) had a BCVA better than 6/18 and 7 eyes (4.1%) had a BCVA of 6/18 to 6/60.Conclusion: Patients undergoing phacoemulsification had a good visual outcome as a result of the procedure performed by cataract surgeon trained from AOCA/NNJS national phacoemulsification training program of Nepal.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6540 Nepal J Ophthalmol 2012; 4 (2): 248-255